Contemporary political ideologies. Movements and regimes / Roy C. Macridis - Macridis, Roy C. (Estados Unidos de America: Little, Brown & Company, 1985)
Political ideologies, democracy, many roots and families, democracy and liberalism, democracy and socialism, democracy and conservatism, england and the U.S.A., communism, from one to many, soviet communism, communist variations, nazism and fascism, the totalitarian right, old wine in new bottlers, nationalisms, revolutions, religion, third world ideologies, revolution and an Act of Will, liberation theology, the voide of the church and the poor.
Content, bibliography, illustrated cover
Col. Soc
Keywords: 1. CONTEMPORARY-POLITICAL ODEOLOGIES 2. POLITICAL IDEOLOGIES 3. SOCIOLOGY